Local government elections: a beacon of ‛service delivery hope’ in South Africa - Tirivangasi, H. M.; Mugambiwa, S. S.; Mutyenyoka, E. M.; Rankoana, S. A. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
This paper assesses the impact of local government elections in addressing service delivery matters. Service delivery protests have become a common phenomenon in South African communities. The reasons attributed to these protests have often been corruption, maladministration, financial challenges and slow rollout of services by authorities in local municipalities. As a result, the frustrated masses are forced to make informed choices through the ballot paper. Local government elections are one of the most popular platforms where South Africans choose candidates of their choice to serve as councillors and mayors in local governments. By voting for a particular candidate, citizens will be empowering politicians with a mandate to make important decisions on their behalf. However, in most cases elected officials are corrupt and frequently feed their communities with empty promises. The study employed an exploratory design and a qualitative method. Snowball sampling was employed in selecting relevant sources which would lead the researchers to other research work on the same field through key words and reference lists. Discourse analysis was employed to analyse data. The study discovered that local government elections are important in ensuring the quality of service delivery the electorate receives.
Journal article, published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Corruption; Local government elections; Maladministration; Municipality; Protest; Service delivery; Local elections -- South Africa; Local government -- South Africa; Municipal government -- South Africa; Political corruption -- South Africa